PM Lee Hsien Loong's speech at the official opening of Singapore Management University law school building and the Kwa Geok Choo Law Library on 15 March 2017 - LEE, Hsien Loong (Institutional Knowledge at Singapore Management University, 2017)
Full text of Prime Minister Lee Hsien Loong speech to open the new SMU law school building and the Kwa Geok Choo Law Library. He reminised about his mother Mdm Kwa Geok Choo, and his thoughts about the future of the legal profession and how the government can support them.